Rational use of glucocorticoids during pregnancy in patients with systemic vasculitis - Alpay Kanıtez, Nilüfer (Acta Medica, 2024)
Glucocorticoids (GC) are important in fetoplacental development and GC production increases in pregnant women.GCs can be used for various reasons during pregnancy, but there are some things to keep in mind.In patients with systemic vasculitis, GC exposure may be associated with complications such as low birth weight and preterm birth. When planning pregnancy in patients with systemic vasculitis, the aim should be to control disease activity with the lowest possible dose of GC. Pregnant women who are required to use GC should also be monitored more closely for gestational diabetes and hypertension.